Interactive software for mapping concentrated displacements in masonry arches - Yuan, Yu; Stockdale, Gabriel; Milani, Gabriele (SoftwareX, 2022)
Arches are an important part of the masonry architectural heritage and also serve as infrastructure for bridges and culverts. The behavior testing and structural health monitoring of masonry arches require effective measurement methods. There have been a lot of testing methods applied regarding this subject, among which the vision-based non-destructive methods are very appealing. However, as the demands of measuring accuracy and range increase, the labor and economic costs expand to uneconomical levels. A novel, cheap, and fast measurement strategy which focuses directly on the mechanical failure of masonry arches has been developed. This strategy termed Behavior Mapping (BM) is based on homography and does not require a high-precision camera or extensive experimental setup. A scale dry-stack arch was subjected to repeated collapses through springing displacements during the proof-of-concept development of BM. This generated a huge amount of data and required the development of a MATLAB® based graphical user interface (GUI). The objective of this article is to introduce the GUI and the accompanying data for the purpose of providing educational insight into the behavior of masonry arches. These educational experimental cases integrated in the GUI provide the possibility to better understand the failure mechanism of dry-stone arch under foot displacement, as well to easily identify the occurrence of mechanical joints and determine the value of deformations. This GUI can also be adapted for different arch configurations, as well for further real-time monitoring.